TRANSFORMAÇÕES SOCIOECONÔMICAS E NO USO DA TERRA EM COMUNIDADES QUILOMBOLAS AMAZÔNICAS DA ILHA DO CAJUAL FRENTE À EXPANSÃO DAS ATIVIDADES PORTUÁRIAS EM ALCÂNTARA/MA - ARAÚJO, Anderson David Martins de (2024)
Port activities are essential for humanity, leading to significant enterprises and expansions that can have a substantial impact on the environment and the lives of local communities. In the case of the Port Complex comprising the Porto do Itaqui, Ponta da Madeira, and Porto da Alumar in São Luís, this expansion has had important economic implications but has also raised environmental concerns and problems for traditional peoples and communities, especially those dependent on fishing and belonging to Ilha do Cajual in Alcântara, MA, within the Amazonian environmental context. In this sense, the central objective of this work was to analyze the changes in economic activities and land use in the face of port activities and the projection of expansion and their impacts on the local population's way of life. The dialectical approach was essential to understand the social contradictions on Ilha do Cajual, offering a framework to identify and analyze dichotomies and factors driving economic changes. The qualitative research used the dialectical methodology to understand the social contradictions on Ilha do Cajual. It was divided into three main stages: literature review, field research, and data analysis. In the first stage, existing data and information were collected and analyzed to establish a solid theoretical foundation. The second stage involved direct observations and semi-structured interviews with local farmers and fishers, complemented by participant observation, to understand regional practices and relationships. In the third stage, the collected data were processed and analyzed to identify patterns and develop sustainable agricultural strategies. The sample included 30 participants (30% of the island's population), selected based on criteria such as involvement in fishing and experience in the activity. Perceptions of nature vary among different groups, with traditional communities having a more cosmological and profound view. The production of nature, allied with a capitalist productive system, often expropriates common goods from local communities, making activities such as fishing and agriculture less viable. On Ilha do Cajual, this is reflected in the decreased productivity of fishing and the growth of agricultural activities, resulting in environmental problems such as loss of native vegetation and soil degradation. The island will face significant changes with the installation of the Private Use Terminal (TUP), occupying 62.14% of the Terra Firme area. This will leave only 37.86% of the remaining Terra Firme. It is considered that the degradation of the Ilha do Cajual environment is linked to external disturbances mainly caused by port activities and their expansion, and in this sense, agricultural practices with low fallow periods generate degradation and suppression of other areas by the advance of livestock.